Implementation of Quality Management of Islamic Religious Education at the Thai Southern Bearing School: Implementasi Manajemen Mutu Pendidikan Agama Islam di Sekolah Bantalian Selatan Thailand - Sueni, Nurufaraai; Zaman, Badrus (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine how the implementation of quality management of Islamic religious education in Southern Thailand schools and to analyze the supporting and inhibiting factors for the implementation of quality management of Islamic religious education in Southern Thailand schools. This study is field research with a qualitative research approach. With data collection techniques using interviews, observation, and documentation, the data that has been obtained is then analyzed. The informants in this study were the head of the Pillowian school, the deputy head of the Pillowian school, teachers, employees, and students who were in the South Pillows school in Thailand. The results of this study are: 1. implementation of quality management of Islamic religious education in Southern Thailand schools applies four principles: a. the principle of equifinality. b. decentralization. c. self-managing; and d. human initiative. 2. Supporting factors for school-based school management. Adapted from a model from schools in Kelantan, the school organizes projects or activities by bringing in speakers from other schools to teach or give lectures and community support, such as helping to keep the school safe. 3. Factors hindering school-based management in improving the quality of Islamic religious education are problems with facilities such as inadequate technology and learning media that cause obstacles in teaching. The way to minimize inhibiting factors such as a lack of facilities and infrastructure is by submitting a proposal to request funds for school development.